Development of 3D graph-based model to examine photovoltaic micro cracks - Dhimish, Mahmoud (H. : ĐHQGHN, 2018)
This paper presents a novel technique to examine the impact of Photovoltaic (PV) micro cracks on the performance of the output power for PV solar cells. Initially, the image of the PV micro crack is captured using Electroluminescence (EL) method, then processed by the proposed technique. The technique consists of two stages, thefirst stage combines two images using an OR gate, the first image is the crack-free (healthy) solar cell, whereas the second is the cracked solar cell image. The output image from the first stage is passed into the second stage which uses a 3D graph-based model in order to examine the output power loss in the cracked solar cell. In order to examine the effectiveness of the 3D graph-based model, two different cracked PV solar cells have been examined. From the obtained results, it is evident that the crack size, location and orientation are more detectable using the developed technique. In addition, the maximum and minimum output power can also be estimated using the offered technique.